A Wild-Type Botrytis Cinerea Strain Co-Infected by Double-Stranded Rna Mycoviruses Presents Hypovirulence-Associated Traits - Castillo-Nara, A; Cottet-Bustamante, L (2013)
Abstract. Background: Botrytis cinerea CCg378 is a wild-type strain infected with two types of double-stranded RNA (dsRNA) mycoviruses and which presents hypovirulence-associated traits. The objectives of the present study were to characterize the mycoviruses and investigate their relationship with the low virulence degree of the fungal host. Results: B. cinerea CCg378 contains five dsRNA molecules that are associated with two different types of isometric viral particles of 32 and 23 nm in diameter, formed by structural polypeptides of 70-kDa and 48-kDa, respectively.The transfection of spheroplasts of a virus-free strain, B. cinerea CKg54, with viral particles purified from the CCg378 strain revealed that the 2.2-kbp dsRNAs have no dependency on the smaller molecules for its stable maintenance in the fungal cytoplasm, because a fungal clone that only contains the 2.2-kbp dsRNAs associated with the 32-nm particles was obtained, which we named B. cinerea CKg54vi378. One of the 2.2 kbpdsRNA segments (2219 bp) was sequenced and corresponds to the gene encoding the capsid protein of B. cinerea CCg378 virus 1 (Bc378V1), a putative new member of the Partitiviridae family.Furthermore, physiological parameters related to the degree of virulence of the fungus, such as the sporulation rate and laccase activity, were lower in B. cinerea CCg378 and B. cinerea CKg54vi378 than in B. cinerea CKg54. Additionally, bioassays performed on grapevine leaves showed that the CCg378 and CKg54vi378 strains presented a lower degree of invasiveness on the plant tissue than the CKg54 strain. Conclusions: The results show that B. cinerea CCg378 is coinfected by two mycoviruses and that the 2.2-kbp dsRNAs correspond to the 32-nm mycovirus genome, which would be a new member of the Partitiviridae family as it has the typical pattern of partitiviruses. On the other hand, the results suggest that the hypovirulence of B. cinerea CCg378 could be conferred by both mycoviruses, since the fungal clone B. cinerea CKg54vi378 presents an intermediate virulence between the CKg54 and CCg378 strains. Therefore, the putative partitivirus would be partially contributing to the hypovirulence phenotype of the CCg378 strain. © 2013 Potgieter et al.; licensee BioMed Central Ltd.